2021
DOI: 10.3390/su13042030
|View full text |Cite
|
Sign up to set email alerts
|

Learning How to Learn from Disasters through a Comparative Dichotomy Analysis: Grenfell Tower and Hurricane Katrina Case Studies

Abstract: We describe two well-established, practice-based Master’s programmes as examples of existing competence development opportunities for practitioners and how such links between theory and practice can be developed and taught within the Higher Education (HE) context. We hypothesise that learning from major failures is essential in linking theory with practice in both engineering and management education. We investigate how to train emergency response teams on coping with, and learning from, rare events; a major c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 94 publications
0
5
0
Order By: Relevance
“…Wan et al 38 have stated that information systems should deliver a method for timely exchange of information and knowledge which allows users to reuse lessons that were previously learnt. 39 While these points highlight the importance of correctly set-up AIMS, there is much documented evidence on the associated challenges. A survey by O'Hanlon 40 showed that only 20% of respondents could describe their AIMS deployment as successful.…”
Section: Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…Wan et al 38 have stated that information systems should deliver a method for timely exchange of information and knowledge which allows users to reuse lessons that were previously learnt. 39 While these points highlight the importance of correctly set-up AIMS, there is much documented evidence on the associated challenges. A survey by O'Hanlon 40 showed that only 20% of respondents could describe their AIMS deployment as successful.…”
Section: Problem Statementmentioning
confidence: 99%
“…Kans 37 points out that data / information requirements of the AIMS should be ascertained concurrent to the functionality requirements. Wan et al 38 have stated that information systems should deliver a method for timely exchange of information and knowledge which allows users to reuse lessons that were previously learnt 39 . While these points highlight the importance of correctly set‐up AIMS, there is much documented evidence on the associated challenges.…”
Section: Problem Statementmentioning
confidence: 99%
“…In the case of destructive fires, even high-quality designed concrete structures are severely affected, and eventually collapse. In 2017, the 24-storey Grenfell Tower in London, England caught fire, which was started by a malfunctioning fridge–freezer on the fourth floor; the event caused 72 deaths and severe structural damage [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Following the 9/11 terrorist attacks, which resulted in the death of more than 2000 people in the United States [6], the understanding of human behaviour under fire situations has changed. However, recent fire disasters, such as the Grenfell Tower disaster in London, present a bleak reminder that, despite the advancements in fire safety, there is still some room to learn from these occurrences and it remains necessary to reflect upon the adequacy of fire safety preparedness [8].…”
Section: Introductionmentioning
confidence: 99%